ANALISIS KEBUTUHAN PERANCANGAN LAYANAN ADMINISTRASI ORGANISASI MAHASISWA MENGGUNAKAN TEKNIK UML - Janessa Sarah Destini,; Tony, (Jurnal Ilmu Komputer dan Sistem Informasi, 2025)
Tarumanagara University's Student and Alumni Institution has an important role in supporting the development of student potential through administrative management of Student Organization (Ormawa) work program documents, such as the Student Executive Board (BEM), Student Representative Council (DPM), Faculty Student Activity Unit (UKMF), and Faculty Student Association (HIMAF). Currently, the process of submitting administrative documents such as Activity Proposals, Activity Permits (SIK), and Accountability Reports (LPJ) is still done manually, causing delays, the risk of losing documents, and the difficulty of monitoring approval status. To overcome these problems, this research conducted a needs analysis to design an integrated and web-based student organization administration service. The application’s analysis and design leverage Unified Modeling Language (UML) techniques to model system requirements in a structured and detailed manner. UML techniques used include use case diagrams to define functionality, activity diagrams to illustrate process flow, sequence diagrams to show inter-component interactions, and class diagrams to illustrate data structures. This study aims to provide a foundation for developing an efficient student organization administration application, reducing the use of paper, and increasing the accuracy and traceability of documents.